2018
DOI: 10.1039/c8cp00142a
|View full text |Cite
|
Sign up to set email alerts
|

Structural signature and transition dynamics of Sb2Te3 melt upon fast cooling

Abstract: Crystalline Sb2Te3 is widely studied due to its important applications in memory materials and topological insulators. The liquid and amorphous structures of this compound as well as the dynamics upon quenching, however, are yet to be fully understood. In this work, we have systematically studied the dynamical properties and local structure of Sb2Te3 at different temperatures using ab initio molecular dynamics simulations. The calculated structure factors agree well with the experimental results. The atomic nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 47 publications
(56 reference statements)
3
25
0
1
Order By: Relevance
“…Previous studies have pointed out that the 4-fold rings ABAB are the basic structural elements for fast phase transition in PCMs [37][38][39][40], which could reduce the stochasticity of nucleation [41]. In our previous work for amorphous Sb 2 Te 3 , we found that these defective octahedrons are connected with each other via 4-fold rings [18]. Highly coordinated (such as 6-fold and 5-fold) octahedrons can provide more structural sites for forming 4-fold ring; therefore, less distorted octahedral motifs in amorphous Bi 2 Te 3 are more conducive to the formation of these 4-fold rings.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Previous studies have pointed out that the 4-fold rings ABAB are the basic structural elements for fast phase transition in PCMs [37][38][39][40], which could reduce the stochasticity of nucleation [41]. In our previous work for amorphous Sb 2 Te 3 , we found that these defective octahedrons are connected with each other via 4-fold rings [18]. Highly coordinated (such as 6-fold and 5-fold) octahedrons can provide more structural sites for forming 4-fold ring; therefore, less distorted octahedral motifs in amorphous Bi 2 Te 3 are more conducive to the formation of these 4-fold rings.…”
Section: Resultsmentioning
confidence: 63%
“…The comparison of the primitive rings for Bi 2 Te 3 and Sb 2 Te 3 at 300 K are computed in figure 6. Similar to glassy state Sb 2 Te 3 [18], 4-fold rings in Bi 2 Te 3 are the dominant structural motif among these n-fold rings, the fraction of which is even larger than Sb 2 Te 3 . Previous studies have pointed out that the 4-fold rings ABAB are the basic structural elements for fast phase transition in PCMs [37][38][39][40], which could reduce the stochasticity of nucleation [41].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The programming speed (i.e., the phase-change rate) can reach sub-nanoseconds, much faster than any other memory device 6 . Due to the exceptional performance, phase-change materials (PCMs) have been intensively studied since their invention in the 1960s 7 , and since then various PCMs have been discovered, such as Ge-Te 811 , Sb-Te 1215 , and Ge-Sb-Te 1621 .…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] As for the amorphous Sb 2 Te 3 , Sb and Te atoms are mostly in defective octahedral sites. 13,14 Due to this similarity of local structures between the crystalline and amorphous states, the two phases can transform to each other without long atomic diffusion. To further improve the performance of Sb 2 Te 3 , researchers managed to add some other elements (such as Al, 15 In, 16 Ag, 17 and Ti 18 ) to Sb 2 Te 3 .…”
mentioning
confidence: 99%